2020
DOI: 10.1186/s13054-020-03007-0
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte ratio as a predictive biomarker for moderate-severe ARDS in severe COVID-19 patients

Abstract: Trial registrationChiCTR, ChiCTR2000029758. Registered 12 February 2020 - Retrospectively registered

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
100
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(114 citation statements)
references
References 5 publications
9
100
0
5
Order By: Relevance
“…In this study, patients with CSI had high NLR and CRP levels and low s-Alb levels, similar to those in previous studies [ [18] , [19] , [20] ]. High NLR is associated with systemic inflammation [ 21 , 22 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, patients with CSI had high NLR and CRP levels and low s-Alb levels, similar to those in previous studies [ [18] , [19] , [20] ]. High NLR is associated with systemic inflammation [ 21 , 22 ].…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies [ 18 , 19 ] reported that NLR can be used to identify high-risk patients with moderate–severe ARDS, with an optimal threshold value of 9.8 [ 18 ] or 3.13 [ 19 ]. Wang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, more and more studies have found that NLR is signi cantly different between the mild/moderate and severe/critical groups, survival and death group in COVID-19 patients. In addition, a series of studies have suggested NLR is a reliable predictor of COVID-19 progression and elevated NLR is associated with high mortality [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Dr. Ma [ 1 ] investigated the neutrophil to lymphocyte ratio (NLR) in predicting moderate-severe acute respiratory distress syndrome (ARDS) in patients with COVID-19 infection. They reported that NLR was significantly higher ARDS group and was a good predictor for moderate-severe ARDS, with area under curve (AUC) 0.749.…”
mentioning
confidence: 99%